“PENAMBANGAN PASIR DAN BATU” SEBAGAI WUJUD SUBSTITUSI KEGIATAN SOSIAL EKONOMI PETANI MASYARAKAT WONOSOBO (Kajian Ekologi Manusia dengan Pendekatan Environmental Determinism dan Sistem Terbuka “ Rambo”) (Forum Ilmu Sosial, 2012)
The Environtmental destroyed had been mortally if no  respectation from all. For thus, we need some respons to avoid them don’t be seriously. The human ecology is being to protect beetwen human relation equilibrium with those environtment. Many of approaches can be applied on human ecology to analyze multy various cases. The Environtmental destroyed case is causes by ferry man of sand is very serious case and urgent to find the problem solving comprehensively. Goals to be achieved is to describe and give perception about causes and reason why the farmer doing some activities (ferry man of sand and stone), give some analysis from the case with a few of human ecology approaches and so give some recomendation for stakeholders to reach of sustainable development with environtmental determinism and openeed system approach from Rambo. The result show that the ferry man of sand and stone is doing by farmer community in Wonosobo region have many of reason. According to the environmental determinism approach, the basic problem which cause those activity is supply of natural resources i.e the sand and stone. So, in this case generally people or farmer community especially is not wrong. In another side this activity is appear causes bay interrelationship between social system and society inner-ecosystem (local farry man) with social system and society outer ecosystem (governmant and foreign farry man). Implications from applied those two approaches need some thinker will be cooperative to get the smart solution.